A Systematic Study on the Effect of the Xanthation Temperature on Viscose Quality - Novita Novita; Budhijanto Budhijanto; Muhammad Mufti Azis (Engineering Proceedings, 2024)
The xanthation reaction is an exothermic reaction between alkali cellulose (AC) and carbon disulfide (CS2) used to regenerate a viscose solution. The cooling system plays an important role during the reaction to yield more of the main product, cellulose xanthate (CX), instead of the by-product, sodium trithiocarbonate (TTC). Minimizing the yield of by-products during the reaction phase may lead to less by-product generation during the ripening process due to free caustic and excess CS2 in the system. The reaction was performed in a batch reactor with an agitator (9.7 rpm) under vacuum conditions (350 mbar), and the temperature varied from 20 °C to 35 °C, as is applicable in industrial plants. Meanwhile, the CX and TTC were determined via UV spectroscopy. Since the temperature reaction will affect the period of the reaction, which impacts the productivity of industrial applications, the experiment was conducted with a temperature change during the reaction to obtain a good-quality product without impacting productivity. This work aimed to reach an optimum xanthation temperature under the same combination of hardwood and softwood dissolving pulp. The results indicated that the xanthation reaction has an advantage at lower temperatures compared to higher ones; however, having a lower temperature led to a longer reaction period. The TTC was shown to be 17.7% lower at lower temperatures than at higher temperatures, which means that the CX was at a higher percentage at lower temperatures. Interestingly, the combination of higher and lower temperatures gave good viscose quality, which may lead to less consumption of CS2 and improve the environment due to less sulfur production during spinning.